La función de la comunicación externa, como instrumento estratégico para mejorar el accionar de la fundación misión sonrisa de la ciudad de Loja, en el periodo noviembre 2016 – agosto 2017 - Chamba Castillo, Guisella Carolina (2019)
The present work has as objective to realize a study on the function of the external communication, like strategic instrument to improve the action of the foundation smile mission of the city of Loja; analyze the effectiveness of communication processes, assess the level of knowledge that citizens have, with the collaboration of the foundation's directors (coordinator and secretary of the foundation), the directors of the elderly centers and the residents of the urban parishes of the city of Loja. In the present thesis the scientific method was used that served to clear the doubts on the subject; the qualitative method helped us to analyze the social extracts present in the Lojana citizenship, the deductive method allowed to analyze the main problem of the investigation, the analytical method was present when analyzing the details, behaviors and characteristics that were presented in the investigation, for order, process and interpret the information collected in the field of study used the statistical method, finally, with descriptive method was able to analyze the communication process used by the foundation to disseminate its actions, deepening and describing fundamental aspects that we they allowed to process the field information the final conclusions and recommendations. Among the main conclusions are: lack of a strategic plan for external communication; lack of knowledge in the citizenship regarding the action of the foundation; incorrect treatment of information in digital media; scant opening of local media. In addition, techniques such as surveys, interviews and observation were used that contributed to possible solutions that contributed to the design of communication tools that contribute to positioning the institution